Post-Transplant Nivolumab Plus Unselected Autologous Lymphocytes in Refractory Hodgkin Lymphoma: A Feasible and Promising Salvage Therapy Associated With Expansion and Maturation of NK Cells - Guolo, Fabio; Minetto, Paola; Pesce, Silvia; Ballerini, Filippo; Clavio, Marino; Cea, Michele; Frello, Michela; Garibotto, Matteo; Greppi, Marco; Bozzo, Matteo; Miglino, Maurizio; Passannante, Monica; et al. (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (CI) have demonstrated clinical activity in Hodgkin Lymphoma (HL) patients relapsing after autologous stem cell transplantation (ASCT), although only 20% complete response (CR) rate was observed. The efficacy of CI is strictly related to the host immune competence, which is impaired in heavily pre-treated HL patients. Here, we aimed to enhance the activity of early post-ASCT CI (nivolumab) administration with the infusion of autologous lymphocytes (ALI). Twelve patients with relapse/refractory (R/R) HL (median age 28.5 years; range 18-65), underwent lymphocyte apheresis after first line chemotherapy and then proceeded to salvage therapy. Subsequently, 9 patients with progressive disease at ASCT received early post-transplant CI supported with four ALI, whereas 3 responding patients received ALI alone, as a control cohort. No severe adverse events were recorded. HL-treated patients achieved negative PET scan CR and 8 are alive and disease-free after a median follow-up of 28 months. Four patients underwent subsequent allogeneic SCT. Phenotypic analysis of circulating cells showed a faster expansion of highly differentiated NK cells in ALI plus nivolumab-treated patients as compared to control patients. Our data show anti-tumor activity with good tolerability of ALI + CI for R/R HL and suggest that this setting may accelerate NK cell development/maturation and favor the expansion of the “adaptive” NK cell compartment in patients with HCMV seropositivity, in the absence of HCMV reactivation.